2016
DOI: 10.1021/acs.jafc.5b04924
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Walnut Peptides–Zinc Complex and Its Antiproliferative Activity against Human Breast Carcinoma Cells through the Induction of Apoptosis

Abstract: The walnut peptides and zinc ions were combined to generate a walnut peptides-zinc complex (WP1-Zn) with enhanced antiproliferative ability as well as reduced toxicity. The result indicated that Zn ions were successfully combined with WP1 through Zn-N and Zn-O covalent bonds. WP1-Zn compounds exhibited strong antiproliferative ability against the selected human cell lines, especially MCF-7 cells, whose survival rate reduced to 20.02% after exposure to 300 μg/mL of WP1-Zn for 48 h. WP1-Zn inhibited MCF-7 cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…To determine the potential protection mechanisms of cerebrosides, we examined the effects of sea cucumber cerebrosides on mitochondria‐dependent apoptosis. Bax is a member of the Bcl‐2 family to activate apoptosis, while the Bcl‐2 protein is associated with anti‐apoptotic activity . As shown in Figure , the relative expression of Bax/Bcl‐2 was significantly increased in A β 1–42 ‐injected rats compared with that of sham group rats.…”
Section: Resultsmentioning
confidence: 89%
“…To determine the potential protection mechanisms of cerebrosides, we examined the effects of sea cucumber cerebrosides on mitochondria‐dependent apoptosis. Bax is a member of the Bcl‐2 family to activate apoptosis, while the Bcl‐2 protein is associated with anti‐apoptotic activity . As shown in Figure , the relative expression of Bax/Bcl‐2 was significantly increased in A β 1–42 ‐injected rats compared with that of sham group rats.…”
Section: Resultsmentioning
confidence: 89%
“…The mitochondrial membrane potential was measured using JC-1 dye [45, 47]. MGC 803 cells were seeded on glass coverslips and treated with geridonin, paclitaxel, or geridonin plus paclitaxel for 24 h. MGC 803 cells were then stained with 5 μg/mL JC-1 (Beyotime Biotechnology) at 37°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharides are natural polymers that exist widely in plants, animals, and microorganisms [3][4][5]. Previous studies have demonstrated that the polysaccharides play a vital role in the life of living organisms [6][7][8]. In particular, plant polysaccharides have attracted much more attention from experts in the food and biomedical fields, due to their biological activities [9][10][11].…”
Section: Introductionmentioning
confidence: 99%